(untitled) (Bangladesh Journal of Botany, 2022)
An experiment was conducted to find out the promising genotype for commercial cultivation in the region. All the genotypes differed in their growth and yield characters. Among the genotypes evaluated, H-68 had the maximum growth characters like tree height, stem girth and canopy spread whereas total laterals/m2, flowering laterals/m2, fruit set/m2, number of nuts per panicle, nut yield/ tree and shelling percentage were maximum in H-303. M- 15/4 showed longest flowering duration. Genotypes H-255 and H-367 had the highest nut weight and apple weight, respectively. Apple TSS was recorded maximum in T. No. 30/1 whereas apple acidity was recorded maximum in M- 15/4. Results showed that the cashew hybrids H-303 and H-68 are promising in the agro-climatic region of Bastar plateau of Chhattisgarh. Bangladesh J. Bot. 51(1): 179-184, 2022 (March)